Teachers attitudes towards students behavioral problems and their correlation with the school social climate in the 5th and 6th grade sections of the I.E.P. Lastenia Rejas, Wilma Sotillo and Hermógenes Arenas de Tacna, year 2011 - Rodriguez Tanta, Maritza Isabel (2013)
Objective: The main objective was to determine the correlation of the teachers' attitudes toward the behavioral problems of the students with the social climate in the school sections of 5th and 6th grade of the I. E. P. Lastenia Rejas, Wilma Sotillo and Hermogenes Arenas. Method: The research is Basic type or pure, with design of descriptive-correlational.The sample consisted of a total of 366 students and 14 teachers, who were administered the surveys of attitudes toward the behavioral problems of the students, while the survey of school social climate was applied to the students. Results:We found the existence of a significant level of correlation between attitudes toward the behavioral problems of the students and the school social climate. A significant majority (64 %) of teachers from the three educational institutions on average show favorable attitudes toward the behavior problems of their students. Conclusions:In general terms it can be stated that a majority of the students and students of the 5th and 6th grade of the three public educational institutions studied in the present investigation submit a social climate positive school (57.3 % ).